Education and Quality of Life: Does the Internet Matter in China? - Zhan, Zhan; Su, Zhi-Wei; Chang, Hsu-Ling (Frontiers in Public Health, 2022)
The Internet has influenced human wellbeing through social networking, time-saving, diffusion of knowledge, and access to health information. Health is a key component of human health and quality of life. This study examines the nexus between education, the internet, and quality of life using China data spanning 1991 to 2020. The study used ARDL to examine the short and long-run explored the education and internet impact of quality of life. Education status plays a significant role in promoting quality of life in the short and long-run. The empirical findings show a significant positive impact of the internet and ICT on the short and long-run quality of life. Financial development and FDI improve quality of life in log-run in China. Subsequently, China policymakers should develop the ICT infrastructure and human capital to support increased quality of life.